THE DIMENSIONS OF PSYCHOLOGICAL WELL-BEING OF CUSTOM EMPLOYEES DURING THE PANDEMIC - Sardiko, Vladislavs; Ilisko, Dzintra; Badjanova, Jeļena; Ignatjeva, Svetlana; Jukšs, Valdis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
There has been a significant increase in interest about a psychological well-being among the researchers, politicians, media and general public. This study focuses on a measurement on a psychological well-being of the custom employees. For the purpose of measurement of a psychological well-being of custom employees, the authors have used Ruff’s scale that includes such components as positive relationships with others, autonomy, competence, personal growth, a purpose in life, and self-acceptance. According to Ryff (2014), well-being has been investigated in relation to one’s career pursuits. The purpose in life and personal growth were found to contribute to career commitments. In the case of the Latvian custom employees, among the essential elements of a psychological well-being are economic factors, favourable work environment and career opportunities in the organization. The study focuses in a psychological well-being of custom employees during the pandemic that leads to conclude that custom employees were in the forefront alongside with the doctors in stabilizing the situation in the county and have experienced a burn out, thereforethey  need a psychological support and a recognition of their efforts at work.